The Structure of Motor Fitness of Young Footballers in a Three-Year Sports Period (Baltic Journal of Sport and Health Sciences, 2018)
In the continuous research, conducted in the sports school in Tarnów (Poland) with a football proﬁ le, the authors attempted to ﬁ nd out whether the changes of hidden predispositions and motor abilities appear during the training process which constitute the foundation for the development of technical and tactic ﬁ tness against the background of the similar research results carried out in the comparative groups of non-training individuals. In the research the measurements of the basic somatic traits, anthropometric indexes, VO 2 max  × kg  –1  and motor skills were taken into consideration. The observations were made every six months for three years. The comparative group consisted of the peers with attending randomly chosen schools (comparative group). The conducted factor analysis revealed the fact that there are minor quantitative differences of the motor structure between training and non-training groups during a three-year observation period. In both the sportsmen’s and less physically active boys’ groups the number of separated factors did not increase as well as the set of variables taken into account. It can be concluded then, that the applied way of sports selection as well as the process of their adaptation to a speciﬁ c training ballast might have been the causative factor of the structure efﬁ ciency speciﬁ cation among children from sports schools. In this connection, they cannot deny the thesis that a talented sports master can be recognized already as a child. Still, the ways of such a selection seem controversial.Keywords: the structure of motor fitness of young footballers, continuous research, factor analysis.